Faktor-Faktor Yang Mempengaruhi Konsumsi Tablet Tambah Darah Pada Ibu Hamil di Puskesmas Buaran - Desi Soraya; Watiah Watiah; Qomariyah Qomariyah (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Anaemia is a global problem for pregnant women. The WHO states that the incidence of anaemia in pregnant women is 48.9%. Central Java's anaemia rate is 57.7%, while Brebes Regency's anaemia rate is 50%. According to the Brebes District Health Office, this problem lies in pregnant women's adherence to taking iron supplement tablets. The study aimed to determine the factors influencing the consumption of blood-supplemented tablets by pregnant women at the Buaran Health Center. This research method was a quantitative analytic survey with a cross-sectional design, with a population of 96 third-trimester pregnant women. The sampling technique was purposive sampling with 49 respondents. The instrument used is a questionnaire. Data analysis was performed univariately and bivariately (using chi-square statistics). The results showed that the factors associated with the consumption of iron tablets were knowledge (p-value=0.013), motivation (p-value=0.037), family support (p-value= 0.019), ANC visits (p-value=0.000), and compliance (p-value=0.002). The suggestion is that pregnant women at the Buaran Health Centre increase awareness about consuming blood-supplemented tablets to maintain the health of the mother and baby and that advice from health workers is needed every time pregnant women carry out an ANC examination at a health facility.